Tinjauan hukum Islam dan penerapannya dalam kehidupan - Azaludin, Shofi (Maliki Interdisciplinary Journal, 2024)
Islamic law is a foundation or benchmark in the teachings of Islam to direct its people towards goodness and truth. These Islamic teachings or laws are teachings revealed by Allah SWT to the Prophet Muhammad SAW and then conveyed to his people so that his servants always carry out these teachings in order to regulate the relationship between humans and humans or humans and their God and even the relationship between humans and the universe. Humans must have an awareness of the importance and even have to do it in order to realize the achievement of a peaceful and harmonious life so as to give birth to a strong tolerance that is produced. In addition, Islamic law also teaches how to act and behave, how to communicate or interact with fellow human beings and establish relationships according to what is taught in Islam. This method is a qualitative method that refers back to the Al-Qur'an, Sunnah, ijma and qiyas